2017
DOI: 10.1186/s40814-016-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Distant delivery of a mindfulness-based intervention for people with Parkinson’s disease: the study protocol of a randomised pilot trial

Abstract: BackgroundPsychological difficulties, especially depression and anxiety, are the most prevalent non-motor symptoms in Parkinson’s disease. Pharmacological treatments for these conditions appear relatively ineffective in Parkinson’s disease. Mindfulness courses are increasingly popular and recognised as effective for managing emotional states, and there is growing evidence for the effectiveness of mindfulness courses for people with long-term medical conditions. With this exploratory pilot trial, we want to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…More details on the protocol of the study have previously been published. 28 All participants completed written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…More details on the protocol of the study have previously been published. 28 All participants completed written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…The efficacy of third wave therapies such as mindfulness, cognitive behaviour therapy and stress management is increasingly being tested for a range of non-motor symptoms in PD [19][20][21][27][28][29] with some positive preliminary results. Large, controlled trials with longer follow up periods are needed.…”
Section: Discussionmentioning
confidence: 99%
“…A challenge of providing these interventions is often one of resource, particularly when a trained therapist is required to implement an intervention. Despite the recent proliferation of online interventions in Parkinson's [27,28] which have clear practical benefits, there was a consensus that an element of face-to-face contact was required in intervention delivery. It is essential to carefully balance the preferences of people with Parkinson's with the practicalities of delivering cost-effective interventions to large groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other trials for therapy involving body awareness training for the treatment of wearing off-related anxiety and a mindfulness-based exercise have shown that these modalities are helpful in balance and well-being. 32,33 Serial electroconvulsive therapy (ECT) has not been well studied but was found to be effective in a case study of severe anxiety in patients with PD. 34…”
Section: Management Of Anxiety In Pdmentioning
confidence: 99%